Normative values for circadian and ultradian cardiovascular rhythms in childhood - Hadtstein, Charlotte; Wühl, Elke; Soergel, Marianne; Witte, Klaus; Schaefer, Franz (Hypertension, 2004)
To assess the prevalence and characteristics of physiological circadian (24-hour) and ultradian (12-, 8-, and 6-hour) rhythms of mean arterial blood pressure (BP) and heart rate (HR), we analyzed 24-hour ambulatory BP profiles from 938 healthy school children aged 5 to 18 years. Cosine harmonics were fitted by Fourier analysis, and an amplitude and acrophase (time of peak) were calculated for each rhythm.